An Analysis of the Impact of Online Games on Students' Spirituality in the Creed and Ethics Subject for Grade VII at MTs Manbaul Ulum Gaya Baru II - Iqbal Firmansyah; Siti Roudhotul Jannah; M. Sayyidul Abrori (Journal of Research in Islamic Education, 2026)
This study aims to determine and analyze the impact of online games on the spirituality of seventh-grade students in the Aqidah Akhlak (Islamic Aqidah) subject at MTs Manbaul Ulum Gaya Baru II. The development of digital technology has led to increased use of online games among students. This phenomenon has created various problems, particularly related to learning behavior and the development of students' spirituality in their daily lives. Some students tend to spend more time playing online games, neglecting their obligations to study, worship, and their responsibilities as students. This study used a descriptive qualitative approach. Data collection techniques included interviews, observation, and documentation. The study subjects were seventh-grade students using a saturated sampling technique. The results showed that online games have both positive and negative impacts on students. Positive impacts include improved concentration, teamwork, and foreign language vocabulary. However, negative impacts were more prevalent, such as decreased concentration in learning, playing until late at night, lack of discipline, and reduced awareness of fulfilling their obligations to study and worship. Therefore, supervision and guidance from teachers and parents are needed so that students are able to use technology wisely and balance learning activities, playing, and developing spirituality in everyday life.